INTEGRATING SHARIA AND MARIFA: TRANSFORMING SHEIKH YUSUF AL-MAKASSARI’S DA’WA METHODOLOGY TOWARD AN INCLUSIVE DIGITAL RELIGIOUS HABITUS - Arifuddin; Andi Aderus; Suriati; Firdaus Muhammad; Akhmad Fathur Fahlevi (Institut Agama Islam Negeri Bone, 2026)
The polarization of contemporary religious discourse between rigid formal-legalism and superficial esoteric spiritualism in the digital sphere has precipitated a crisis of authority and social fragmentation that extensively threatens the stability of the global Muslim community. Although extant literature has widely explored classical thought, a significant methodological lacuna remains concerning the transformation of the 17th-century Sufi-jurisprudential synthesis as a strategic antithesis to ideological radicalism and the attenuation of religious meaning within the current cyber ecosystem. This research undertakes a scholarly intervention through a Gadamerian hermeneutic approach to the authentic manuscripts of Sheikh Yusuf Al-Makassari to reconstruct a multidimensional da’wa framework that coherently integrates the levels of sharia, tariqa, haqiqa, and marifa as structures for social transformation. The analysis reveals that the integration of these exoteric and esoteric dimensions fosters a solution-oriented religious ethic, wherein the models of da’wa bil-hikmah and mau'idzah hasanah are reactualized as instruments to counteract hate narratives and reconstruct an integrative religious habitus. Theoretically and practically, this study contributes to the development of authentic digital da’wa models, the reinforcement of egalitarian religious authority, and the provision of discursive solutions to the fragmentation of the ummah through an approach that is contextually adaptive yet doctrinally grounded in the post-truth era.